Photosynthetic capacity and water use efficiency in sugarcane genotypes subject to water deficit during early growth phase - Silva,Marcelo de Almeida (2013)
The objective of this study was to compare the gas exchange, photosynthetic capacity and water potential of sugarcane genotypes cultivated under water deficit conditions imposed during the initial growth phase. Experiments were performed in a greenhouse using two sugarcane genotypes namely: HoCP93-776 (drought susceptible) and TCP02-4587 (drought tolerant). Sixty days after planting, two different water treatments were applied (i.e., with or without water deficit). At 0,30 and 60 days after the treatment, gas exchange variables were evaluated for their relationship with water use, intrinsic instantaneous water use efficiency and instantaneous carboxylation efficiency. The SPAD index, photosynthetic pigments, water potential and relative water content in the leaves were also analyzed. The genotype HoCP93-776 was more sensitive to drought treatment as indicated by the significantly lower values of SPAD index, photosynthetic pigments, water potential (Ψw) and relative water content (RWC) variables. The genotype TCP02-4587 had higher water potential, stomatal control efficiency, water use efficiency (WUE), intrinsic instantaneous water use efficiency (WUEintr), instantaneous carboxylation efficiency and photosynthetic capacity. The highest air vapor pressure deficit during the drought conditions could be due to the stomatal closing in the HoCP93-776, which contributed to its lower photosynthetic capacity.